Gambaran Skor Plak dengan Berbagai Bentuk Sikat Gigi dan Metode Menggosok Gigi Pada Siswa Kelas V dan VI SD Negeri 1 Sidayu - Farah Faridah; Dwi Suyatmi; Sutrisno Sutrisno (Journal of Oral Health Care, 2017)
Brushing toothis the most effective way to clean plaque. Plaque is a thin layer consisting of solid and accumulates microorganisms and attached to the tooth surface. Tooth brush is a tool which can be used to clean mouth and tooth. The purpose of this experiment to reveal the plaque scores with various forms of tooth brush and tooth brushing method in class V and VI Elementary School 1 Sidayu, with the amount of 40 students. Inspected aspects in this experiment are plaque scores, forms of tooth brush and brushing tooth methods. This experiment is using kind of descriptivequantitative experiment. Presentation of data is processed and analyzed by cross tabulation. The results of this experiment based on the gender are 23 male students and 17 female students. In the other side, based on age, there are 13 students having age of 12 at the most. Brushing tooth method that the most respondent used is a combination method which have sum of 24 respondents(60%), while the most tooth brush form used by respondents is flat tooth brush bristle with the sum 25 respondents (62,5%). In the conclusion, based on cross tabulation between plaque scores, tooth brush form and brushing tooth methods, the plaque score of student class V and VI is bad criteria with using flat tooth brush bristle and using combination method of brushing tooth. The sum of those respondents is 60%.